2010
DOI: 10.1094/mpmi-23-2-0139
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana Cells: A Model to Evaluate the Virulence of Pectobacterium carotovorum

Abstract: Pectobacterium carotovorum are economically important plant pathogens that cause plant soft rot. These enterobacteria display high diversity world-wide. Their pathogenesis depends on production and secretion of virulence factors such as plant cell wall-degrading enzymes, type III effectors, a necrosis-inducing protein, and a secreted virulence factor from Xanthomonas spp., which are tightly regulated by quorum sensing. Pectobacterium carotovorum also present pathogen-associated molecular patterns that could pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The use of phyto-compounds is novel and attractive when particularly these virulence factor inhibitors are non-toxic and have no adverse effect on the beneficial bacterial consortia of the host at the used concentration. Concomitantly, Terta et al (2010) reported that A. thaliana cells could be an alternative tool to evaluate the virulence of Pectobacterium spp. Moreover, they observed pathogenicity caused by Pectobacterium sp.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…The use of phyto-compounds is novel and attractive when particularly these virulence factor inhibitors are non-toxic and have no adverse effect on the beneficial bacterial consortia of the host at the used concentration. Concomitantly, Terta et al (2010) reported that A. thaliana cells could be an alternative tool to evaluate the virulence of Pectobacterium spp. Moreover, they observed pathogenicity caused by Pectobacterium sp.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…40 An A. thaliana cell suspension was incubated (24 h) in their culture medium in presence of different concentrations of LPS with or without the appropriate pharmacological effectors. Then, cells (500 mL) were incubated for 10 min in 1 mL phosphate buffer (0.1 M -pH 7) supplemented with Evans Blue to a final concentration of 0.001%.…”
Section: Cell Death Quantificationmentioning
confidence: 99%
“…This type of cell death resembles the one detected during the early phase of infection of A. thaliana suspension cells with P. carotovorum. 40 Upon co-culture of plant cells with 10 8 cfu.mL ¡1 Pcc an early small increase in plant cell death occurred during the first 3 h before pectate-lyase activities were detectable, 40 with dead cells displaying plasmolysis. After 12 h and pectate lyase activity increase, plant cell death largely increased and cell integrity was not preserved ( 40 and Fig.…”
Section: Lps From Pectobacterium Sp Induces Cell Death In a Thalianamentioning
confidence: 99%
See 2 more Smart Citations